NORMAL SEXUALITY OR PATHOLOGICAL SEXUALITY? ANALYSIS OF THE DICHOTOMOUS SEXUALITY CONCEPTION OF THE PSYCHOANALYST OTTO KERNBERG - Szuzter, Daniela (2013)
This article proposes the analysis of the dichotomous conception of normal/pathological sexuality presented in the book “Love  Relations: Normality and Pathology”, by psychoanalyst Otto Kernberg, so as to question the traditional way in which human sexuality is conceived.